Epigenetics and expression of key genes associated with cardiac fibrosis: NLRP3, MMP2, MMP9, CCN2/CTGF and AGT - Chandra, Sruti (Epigenomics, 2021)
AIMS: Excessive inflammatory signaling and pathological remodeling of the extracellular matrix drive cardiac fibrosis and require changes in gene expression. MATERIALS AND METHODS: Using bioinformatics, both tissue-specific expression profiles and epigenomic profiles of some genes critical for cardiac fibrosis were examined, namely, NLRP3, MMP2, MMP9, CCN2/CTGF, AGT (encodes angiotensin II precursors) and hsa-mir-223 (post-transcriptionally regulates NLRP3). RESULTS: In monocytes, neutrophils, fibroblasts, venous cells, liver and brain, enhancers or super-enhancers were found that correlate with high expression of these genes. One enhancer extended into a silent gene neighbor. These enhancers harbored tissue-specific foci of DNA hypomethylation, open chromatin and transcription factor binding. CONCLUSIONS: This study identified previously undescribed enhancers containing hypomethylated transcription factor binding subregions that are predicted to regulate expression of these cardiac fibrosis-inducing genes.